Hadith #2885 - Sahih al-Bukhari - Ubaidullah bin Abi Rafi' عبيد الله بن أبي رافع (Sahih al-Bukhari)
I heard `Ali saying, “Allah’s Messenger (ﷺ) sent me, Az-Zubair and Al-Miqdad somewhere saying, ‘Proceed till you reach Rawdat Khakh. There you will find a lady with a letter. Take the letter from her.’ ” So, we set out and our horses ran at full pace till we got at Ar-Rawda where we found the lady and said (to her). “Take out the letter.” She replied, “I have no letter with me.” We said, “Either you take out the letter or else we will take off your clothes.” So, she took
Grade: Sahih